Digital Communication Strategy to Counteract the Use of Social Media as a Propaganda Tool for Terrorist Groups - Yudho, Amdex Dwi Satyo; Afifuddin, Mochammmad; Suhirwan, Suhirwan (CV. Rayyan Dwi Bharata, 2025)
Social media has become a critical tool for terrorist groups like ISIS and Al-Qaeda, leveraging these platforms to disseminate ideology, recruit members, and mobilize support. This study aims to identify the patterns of terrorist propaganda on social media and develop effective digital communication strategies to counteract these activities. The research employs a qualitative approach through literature review and content analysis, grounded in digital communication, strategy, and propaganda theories. The findings reveal that terrorist groups utilize emotional narratives to disseminate ideology, personalized approaches for recruitment, and social media to organize collective actions. Successful digital communication strategies include AI-based early detection, culturally relevant counter-narratives, digital literacy to raise public awareness, cross-sector collaboration, and robust law enforcement. The study's holistic approach is essential to counter terrorist propaganda, emphasizing close collaboration among governments, technology companies, and society. Further research is recommended to explore emerging technologies and innovative strategies to address the evolving threat.